Analysis of groundwater level fluctuations and groundwater quality at Benoa and Tanjung Benoa Village, Bali Province, Indonesia - Ardana, Putu Doddy Heka; Soriarta, I Ketut; Affandi, Muhammad (Jurnal Teknika, 2024)
Benoa and Tanjung Benoa Village in Badung Regency is growing every year. Population growth impacts the increasing demand for clean water, which groundwater dominates. This affects the fluctuation of groundwater level and groundwater quality. This research method is descriptive and quantitative based on field observation and laboratory tests. Groundwater level fluctuations were observed for 12 months to determine the difference between the rainy and dry seasons. This research aims to determine changes in the dynamics of groundwater conditions in the Benoa and Tanjung Benoa villages. Based on the analysis results, the groundwater table fell 0.9 m in the dry season and rose 0.74 m in the wet season. The minimum pH value was 6.01; the maximum pH was 7.24. The average conductivity was 921-1,003 μs/cm. The average water temperature was 27.4˚C to 28.2˚C. The lowest chloride concentration averaged 68.69-76.40 mg/L, and the highest was 92.3-98.8 mg/L. Dissolved oxygen ranged from 5.9 to 7.2 mg/L.